Adaptive Ephemeral Interiority: Upcycling Site Specific Interiors - Sosa, Marco; Ahmad, Lina; Musfy, Karim (UI Scholars Hub, 2022)
Adaptive reuse in architecture refers to the process of redesigning, converting, and reappropriating existing spaces for functions different from the ones they were originally designed for. This research is a case study showing an alternative to this concept, re-purposing aviation parts and finding new programmatic functions in the design learning studio. The pedagogy approach, adopted by a design studio in the United Arab Emirates (UAE), presents the fluidity of adaptive interiority against rigidity and site specificity. The research results in the creation of adaptive modular spaces and ephemeral interiority through upcycling design, flexibility, materiality, reusability, recyclability, and connectivity while simultaneously showcasing the rigorous interplay of innovation, research, science, and technology. The case study design studio was based at Zayed University and partnered with Etihad Airways, the national carrier of the UAE, highlighting the importance of industry and education as interdisciplinary collaborations. The paper looks at the pedagogical approach and examines the conducted process and evaluates the outcomes and shortcomings, including those inflicted by the COVID-19 world health pandemic. It argues for ‘adaptive interiority,’ inclusion in the adaptive reuse framework and a further reflection on the large vision and possible future impact within the UAE’s social and architectural context.